2010
DOI: 10.1007/s00535-010-0321-6
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of animal models of post-infectious/post-inflammatory irritable bowel syndrome

Abstract: Different methods have been used for the development of post-infectious or post-inflammatory IBS models. Each model has its weaknesses and strengths. More studies are needed to establish post-infection IBS models using more common pathogens. A standard protocol in developing TNBS-induced post-inflammatory IBS model is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 105 publications
0
72
0
Order By: Relevance
“…This colitis is transient, peaking several days after administration and then spontaneously healing such that by 28 days following administration the histology of the colon and myeloperoxidase levels do not differ from untreated animals (Hughes et al, 2009a;Hughes et al, 2009b;Krauter et al, 2007;Qin et al, 2011). However, colonic afferent nerves remain sensitized to distension long after the mucosa heals, which models aspects of the chronic visceral hypersensitivity (CVH) experienced by IBS patients (Gschossmann et al, 2004;Hughes et al, 2009a;Hughes et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…This colitis is transient, peaking several days after administration and then spontaneously healing such that by 28 days following administration the histology of the colon and myeloperoxidase levels do not differ from untreated animals (Hughes et al, 2009a;Hughes et al, 2009b;Krauter et al, 2007;Qin et al, 2011). However, colonic afferent nerves remain sensitized to distension long after the mucosa heals, which models aspects of the chronic visceral hypersensitivity (CVH) experienced by IBS patients (Gschossmann et al, 2004;Hughes et al, 2009a;Hughes et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Delivered at different phases of the life cycle, such stressors may trigger risk factors for visceral hypersensitivity. Accumulating evidence suggests that the internal and external validity of such models is adequate particularly with regard to species, specific gender, age and strain (Larauche et al, 2011;Qin et al, 2011). In contrast to human studies, in which self-reported responses to gut distension can be measured, pseudoaffective markers of the nociception in animal studies are needed.…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
“…Intracolonic 2,4,6-trinitrobenzene sulfonic acid (TNBS) in rodents has been widely used as a model of colitis (23), and recently TNBS has been advanced as a model of postinflammatory colorectal hypersensitivity and thus a model of PI-IBS (20). Hughes et al (14) reported, for example, an inflammation-associated increase in colorectal afferent sensitization and a long-lasting sensitization of serosal and mesenteric class afferents after resolution of TNBS-induced colorectal inflammation.…”
mentioning
confidence: 99%